2014
DOI: 10.1210/jc.2013-2756
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sex on Insulin Secretion in Cystic Fibrosis

Abstract: Surprisingly, in CF, adult women presented higher insulin secretion than adult men at a comparable level with what is observed in healthy individuals. Potential implications of this sex dimorphism in CF remain to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 30 publications
3
30
0
1
Order By: Relevance
“…Moreover, the importance of insulin on clinical status in these patients is further observed in the randomized CFRD trial as well as other uncontrolled studies which have shown that insulin introduction in patients with CFRD can potentially improve nutritional and pulmonary status [12]. As observed in a previously published study, we also observed a higher proportion of woman in the group that presented high I60 [28]. To establish high G60 and/or I60 as a predictive marker of patients at risk of clinical deterioration, further studies, prospective and mechanistic, are mandatory in order to understand the difference between patients with low I60 and high G60 and the relationship between lower pulmonary function, lower nutritional status, hyperglycemia and lower insulin sensitivity.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, the importance of insulin on clinical status in these patients is further observed in the randomized CFRD trial as well as other uncontrolled studies which have shown that insulin introduction in patients with CFRD can potentially improve nutritional and pulmonary status [12]. As observed in a previously published study, we also observed a higher proportion of woman in the group that presented high I60 [28]. To establish high G60 and/or I60 as a predictive marker of patients at risk of clinical deterioration, further studies, prospective and mechanistic, are mandatory in order to understand the difference between patients with low I60 and high G60 and the relationship between lower pulmonary function, lower nutritional status, hyperglycemia and lower insulin sensitivity.…”
Section: Discussionsupporting
confidence: 83%
“…The thresholds associated with risk of accelerated weight and lung function loss would be more relevant. Since CF patients present a specific OGTT pattern characterized by early glucose excursions with rapid normalization as well as major defects in early insulin secretion, OGTT intermediate time points rather than fasting and 2-h values could provide more pertinent information in identifying an association between glucose and/or insulin and clinical deterioration [5,28,29]. The prevalence of glucose abnormalities identified with the OGTT is important in children (23 to 44 %) as well as in adults (around 60 %) [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of diabetes in cystic fibrosis is higher in women than men, despite higher relative insulin secretion in CF women [71]. Although we found no differences between genders of pigs, the number per gender was small and thus our studies were poorly powered to pick up gender differences.…”
Section: Discussionmentioning
confidence: 72%
“…Battezzati et al 33 objetivaron que la producción de insulina durante el OGTT alcanzaba unos niveles similares a los controles sanos, a pesar de la disfunción de la célula ␤ y la alteración en la secreción de insulina en la fase precoz en los pacientes con CF, sugiriendo que la tasa de secreción absoluta de insulina (o el AUC 0-120 de insulina) no es una medida precisa para describir los defectos en la función de la célula ␤, y que el retraso en la secreción de insulina y la secreción total son factores distintos que afectan a la tolerancia a la glucosa. Sin embargo, otros autores encuentran una disminución en la secreción total de insulina al comparar el AUC 0-120 de los casos de CF frente a controles sanos 23,37 .…”
Section: Discussionunclassified